Dukungan Sosial Orangtua dan Guru dalam Mengembangkan Kemandirian Anak Autisme - Melani Aprianti; Aulia Kirana; Alita Randiyani (Fakultas Psikologi Universitas Tarumanagara, 2018)
Children with autism have difficulties in their cognitive function, language, behavior, and social interaction. Teachers and parents have an important role to educate and take care of autistic children to achieve their independence. One form of environmental role in helping the autonomy of children with autism is social support. In order to improve the child's ability, treatment should be comprehensively between parent, psychologist (counselor), psychiatrist, teacher and therapist. But in reality, the handling of children with autism requires a very expensive cost. Unfortunately, many autistic children are unable to afford those therapies because the cost is too high. This research intends to study the social support of teachers and parents in children with autism who cannot afford any therapies to help the children independently. Therefore the support from teachers and parents become very crucial in developing their independence, because they do not have other resources to train autistic children. This research is qualitative research, with purpose to obtain a complete picture of the respondents’ experiences to the circumstances they experienced. The respondents in this research are parent and teacher. We also interview the child’s relatives, who knows the parent and the teacher, to validate their stories. The results show that with their economic limitation, both parent and teacher try to develop the autistic children to be independent, through tangible assistance, informational support and emotional support.